Quantum key distribution using decoy state protocol - Ali, Sellami; Saharudin, Shuhairi; Wahiddin, Mohamed Ridza (Science Publications, 2009)
Problem statement: Quantum key distribution provides unconditional security guaranteed by the fundamental laws of quantum physics. Unfortunately, for real-life experimental set-ups, which mainly based on faint laser pulses, the occasional production of multi-photons and channel loss make it possible for sophisticated eavesdroppers to launch various subtle eavesdropping attacks including the Photon Number Splitting (PNS) attack. The decoy state protocols recently proposed to beat PNS attack and to improve dramatically distance and secure key generation rate of Quantum Key Distribution (QKD).